Onkocelebryta czy zatroskany duszpasterz? Wizerunek medialny ks. Jana Kaczkowskiego w filmie Johnny i wybranych publikacjach na kanale Youtube - Zielińska, Kinga (Łódzkie Studia Teologiczne, 2025)
In this article, the author dedicates special attention to the media activity of Father Jan Kaczkowski. The analysis of audiovisual materials focuses on the author’s series of vlogs „Smak Życia”, published on YouTube, and on the feature film „Johnny” directed by Daniel Jaroszek, which was created based on the biography of Father Jan Kaczkowski. The work proves that the vlogs created by Father Kaczkowski are characterized by a personal style of communication and a clear image of a clergyman – a priest-guide, humorist, lover of good food, while in the film we are dealing with a multi-layered image, condensed in a film story – definitely positive.